Selective Grammatical Convergence: Learning From Desirable Speakers. Issue 8 (16th November 2016) - Lev-Ari, Shiri
Abstract : Models of language learning often assume that we learn from all the input we receive. This assumption is particularly strong in the domain of short-term and long-term grammatical convergence, where researchers argue that grammatical convergence is mostly an automatic process insulated from social factors. This article shows that the degree to which individuals learn from grammatical input is modulated by social and contextual factors, such as the degree to which the speaker is liked and their social standing. Furthermore, such modulation is found in experiments that test generalized learning rather than convergence during the interaction. This article thus shows the importance of the social context in grammatical learning and indicates that the social context should be integrated into models of language learning.